German-occupied Europe in the Second World War - Scheck, Raffael, 1960- 1960- Herausgeber; Théofilakis, Fabien 1976- Herausgeber; Torrie, Julia S., 1973- 1973- Herausgeber (Routledge studies in Second World War history, 2019)
"Inspired by recent works on Nazi empire, this book provides a framework to guide occupation research with a broad comparative angle focusing on human interactions. Overcoming national compartmentalization, it examines Nazi occupations with attention to relations between occupiers and local populations and differences among occupation regimes. This is a timely book which engages in historical and current conversations on European nationalisms and the rise of right-wing populisms"--